2014
DOI: 10.1093/mnras/stu1749
|View full text |Cite
|
Sign up to set email alerts
|

Time correlation between the radio and gamma-ray activity in blazars and the production site of the gamma-ray emission

Abstract: In order to determine the location of the gamma-ray emission site in blazars, we investigate the time-domain relationship between their radio and gamma-ray emission. Light-curves for the brightest detected blazars from the first 3 years of the mission of the Fermi Gamma-ray Space Telescope are cross-correlated with 4 years of 15 GHz observations from the OVRO 40-m monitoring program. The large sample and long light-curve duration enable us to carry out a statistically robust analysis of the significance of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
113
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 138 publications
(134 citation statements)
references
References 47 publications
(44 reference statements)
21
113
0
Order By: Relevance
“…This arises from the low fraction (7%) of gamma-ray loud sources in the radio-weak sample (Figure 11, right), as compared to the higher 50% fraction of gamma-ray loud sources in the radio-strong sample (Figure 11, middle), as expected due to the known radio-gammaray flux correlation in blazars (e.g. Ackermann et al 2011a;Max-Moerbeck et al 2014). This selection bias, combined with the significantly higher m5 of radio-weak sources relative to the radio-strong sources (Section 5.1), dilutes the relationship between m5 and gamma-ray loudness clearly seen when they are separated by flux density.…”
Section: Gamma-ray Loudnessmentioning
confidence: 63%
“…This arises from the low fraction (7%) of gamma-ray loud sources in the radio-weak sample (Figure 11, right), as compared to the higher 50% fraction of gamma-ray loud sources in the radio-strong sample (Figure 11, middle), as expected due to the known radio-gammaray flux correlation in blazars (e.g. Ackermann et al 2011a;Max-Moerbeck et al 2014). This selection bias, combined with the significantly higher m5 of radio-weak sources relative to the radio-strong sources (Section 5.1), dilutes the relationship between m5 and gamma-ray loudness clearly seen when they are separated by flux density.…”
Section: Gamma-ray Loudnessmentioning
confidence: 63%
“…From that combination it follows that the γ-ray emission region is best constrained to a distance of (1.9 ± 1.1) pc away from the jet base. In a similar study, Max-Moerbeck et al (2014) obtain a time lag of (−40 ± 13) d between the leading γ rays and the lagging 15 GHz radio emission. Following their reasoning, this time lag translates into a relative distance of (2 ± 1) pc between the 15 GHz unit-opacity surface and the γ-ray site.…”
Section: Localizing the γ-Ray Emissionmentioning
confidence: 67%
“…Note that in Figure 14 we show the light curves on a logarithmic scale with a fixed dynamic range in order to facilitate direct comparison with Figure 7; on a linear plot both the γ-ray and the radio flare appear strikingly peaked. Based on the statistical properties of Fermi-LAT and OVRO 15GHz light curves, Max-Moerbeck et al (2014) have shown that the γ-ray and the radio flare are likely causally related. During most of the flaring activity in 2012, Mrk 421 was very close to the Sun on the sky, which resulted in relatively poor multiwavelength coverage.…”
Section: Brief Summary Of the Flaring Activity In 2012mentioning
confidence: 99%